2021
DOI: 10.1002/ejoc.202100614
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient heterogeneous V2O5@TiO2 catalyzed the rapid transformation of boronic acids to phenols

Abstract: A V2O5@TiO2 catalyzed green and efficient protocol for the hydroxylation of boronic acid into phenol has been developed utilizing environmentally benign oxidant hydrogen peroxide. A wide range of electron‐donating and the electron‐withdrawing group‐containing (hetero)aryl boronic acids were transformed into their corresponding phenol. The methodology was also applied successfully to transform various natural and bioactive molecules like tocopherol, amino acids, cinchonidine, vasicinone, menthol, and pharmaceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Initially, the catalyst screening is performed with V 2 O 5 /TiO 2 catalysts, i.e., C-05, C-10, C-20, and C-30, containing variable V 2 O 5 contents of 5, 10, 20, and 30% supported over TiO 2 , respectively (Figure ). It was observed that C-05 and C-10 catalyst gives low yields (Table , entries 1–2). Thus, out of these four catalysts, C-20 and C-30 were suitable for this transformation as they gave a high yield and required a shorter reaction time compared to C-05 and C-10 catalysts (Table , entries 3–4).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the catalyst screening is performed with V 2 O 5 /TiO 2 catalysts, i.e., C-05, C-10, C-20, and C-30, containing variable V 2 O 5 contents of 5, 10, 20, and 30% supported over TiO 2 , respectively (Figure ). It was observed that C-05 and C-10 catalyst gives low yields (Table , entries 1–2). Thus, out of these four catalysts, C-20 and C-30 were suitable for this transformation as they gave a high yield and required a shorter reaction time compared to C-05 and C-10 catalysts (Table , entries 3–4).…”
Section: Resultsmentioning
confidence: 99%
“…Together, these catalytic observations give a clear indication of the conditions for generating phenol from the activation of arylboronic acids using the reported copper(II) NHC complex in water. This C-O bond forming reaction has been shown to have significant merit on its own [23,[41][42][43][44][45][46], but it also provides insight into conditions where phenol generation is limited. C-O bond formation occurs in a similar pathway to other CEL bond forming processes but requires higher energy conditions (high temperature) and carefully controlled pH.…”
Section: Discussionmentioning
confidence: 99%
“…Shi group transferred aryl borides to phenols with trichloroacetonitrile as an activator under blue LED, and steride derivatives underwent this condition 228 . Another work of converting aryl borides to phenols was reported by Maurya, and many bioactive molecules could be late-stage hydroxylated ( Scheme 14 b) 229 . Jiao and coworkers used DMSO as an oxygen source to transfer simple organobromides or olefins to bromohydrins, and the hydroxybromination of (+)- δ -tocopherol derivative underwent to produce the corresponding product ( Scheme 14 c) 230 .…”
Section: Oxygenation Of Bioactive Compoundsmentioning
confidence: 99%